Avaliação da resistência ao desgaste de aços inoxidáveis conformados por spray - Beraldo, Leamar Guedes (Universidade Federal de São Carlos, 2011)
The aim of this work was the study of the microstructure and the wear resistance of two stainless steels, the ferritic-AIF with 27% Cr and the superduplex-SDM modified with boron (3.5% wt.), processed by spray forming. The rapid solidification promoted by this process has resulted in the formation of a new structure with refined grains and metastable phases. The deposits, weighing about 3.5 kg, were characterized by combination of scanning electron microscopy (SEM), hardness, micro hardness and wear resistance according to ASTM G65-04. The deposits of AIF and SDM showed more refined microstructure and higher hardness in respect to materials produced by conventional casting. The wear resistance of the SDM was higher than the materials tabulated in ASTM G65-04, namely, AISI D2 tool steel and Stellite 1016, while the AIF presented an intermediary value between these two materials. The addition of boron to the SDM is associated with the formation of borides and led to an increase in the hardness and wear resistance of this spray formed material.
Evaluation of the wear resistance of spray formed stainless steel
Keywords: Aço inoxidável; Desgaste; Conformação por spray; Caracterização microestrutural; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA